2010
DOI: 10.2106/jbjs.h.01236
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Compared with Static External Fixation of Unstable Fractures of the Distal Part of the Radius

Abstract: Continuous dynamic traction with a dynamic external fixator compares favorably with the use of static external fixators for the treatment of unstable fractures of the distal part of the radius.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…54.2%, (2.) 47.3%Dahl classificationPre- and postop IV cephazolin open # IV gentamicin and ornidazole TBSDaily showering and - group 1: brushing the pin sites with soap and a soft toothbrush; group 2: cleaning the crusts using sterile gauze impregnated with 10% polyvinylpyrrolidone iodine (Polyod)1 parenteral AB, two premature fixator removalsChecketts 1995 [28]Dynamic axial fixator.134Adult, tibial shaft #1053.5 monthsRetrospectiveNM39%Minor or majorProphylactic, third-generation cephalosporinNot mentionedRepositioning in 1 patient, removal in 1 patientCheung et al 2008 [8]Hinged external fixators of the elbow100Fractures of the elbow8–94 (31)NMRetrospective25%25%Minor or major75% received a course of postoperative prophylactic oral antibioticsPatients were educated on pin care and were instructed to clean the pin sites with peroxide solution daily.4× early removalDavies et al 2005 [15]External fixation120Fractures or limb reconstructions24–92NMProspectiveNMA, 89.1%; B, 64.9%Episode of pain/inflammation at pin site, + discharge + on bacterial culture or responded to antibioticsNMGroup A: care of the pin site according to local custom; group B: the Russian Ilizarov Scientific Centre technique a Oral AB, removal of the pin or IV AB (numbers not mentioned)Egol et al 2006 [6]External fixation devices118Unstable or displace fractures of the distal radiusAverage 41.3>6 monthsProspective, randomized19%10.1%Requiring oral antibioticsThree doses of IV cephalosporin(1) Weekly dry dressing changes without pin-site care, (2) daily pin-site care with a solution of 1/2 normal saline and 1/2 hydrogen peroxide, (3) placement of a weekly changed chlorhexidine-impregnated disc (Biopatch) around the pinsOral antibiotics 10.1%Hove et al 2010 [29]Dynamic (Dynawrist) and static external fixation (Hoffman II Compact)70Unstable fractures of the distal radiusMean 4212 monthsProspective, randomizedNM43% dynamic 11% static ( p  < 0.01)NMNMNMLocal wound cleaning or treatment with antibiotics. No pins removed prematurelyHutson and Zych 1998 [30]Illizarov system135Periarticular fractures of the tibia and fe...…”
Section: Discussionmentioning
confidence: 99%
“…54.2%, (2.) 47.3%Dahl classificationPre- and postop IV cephazolin open # IV gentamicin and ornidazole TBSDaily showering and - group 1: brushing the pin sites with soap and a soft toothbrush; group 2: cleaning the crusts using sterile gauze impregnated with 10% polyvinylpyrrolidone iodine (Polyod)1 parenteral AB, two premature fixator removalsChecketts 1995 [28]Dynamic axial fixator.134Adult, tibial shaft #1053.5 monthsRetrospectiveNM39%Minor or majorProphylactic, third-generation cephalosporinNot mentionedRepositioning in 1 patient, removal in 1 patientCheung et al 2008 [8]Hinged external fixators of the elbow100Fractures of the elbow8–94 (31)NMRetrospective25%25%Minor or major75% received a course of postoperative prophylactic oral antibioticsPatients were educated on pin care and were instructed to clean the pin sites with peroxide solution daily.4× early removalDavies et al 2005 [15]External fixation120Fractures or limb reconstructions24–92NMProspectiveNMA, 89.1%; B, 64.9%Episode of pain/inflammation at pin site, + discharge + on bacterial culture or responded to antibioticsNMGroup A: care of the pin site according to local custom; group B: the Russian Ilizarov Scientific Centre technique a Oral AB, removal of the pin or IV AB (numbers not mentioned)Egol et al 2006 [6]External fixation devices118Unstable or displace fractures of the distal radiusAverage 41.3>6 monthsProspective, randomized19%10.1%Requiring oral antibioticsThree doses of IV cephalosporin(1) Weekly dry dressing changes without pin-site care, (2) daily pin-site care with a solution of 1/2 normal saline and 1/2 hydrogen peroxide, (3) placement of a weekly changed chlorhexidine-impregnated disc (Biopatch) around the pinsOral antibiotics 10.1%Hove et al 2010 [29]Dynamic (Dynawrist) and static external fixation (Hoffman II Compact)70Unstable fractures of the distal radiusMean 4212 monthsProspective, randomizedNM43% dynamic 11% static ( p  < 0.01)NMNMNMLocal wound cleaning or treatment with antibiotics. No pins removed prematurelyHutson and Zych 1998 [30]Illizarov system135Periarticular fractures of the tibia and fe...…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also found good to excellent results with an external fixator allowing wrist mobility (Hayes et al, 6 Hove et al, 4 Gradl et al 7 ) Non-bridging external fixation was found to offer a reliable method of maintaining radiological reduction of unstable distal radius and to give a good functional outcome after 1 year by Anderson et al 12 Our study revealed significant advantage in terms of anatomical restoration and early functional outcome of early dynamization using the modified JESS fixator for displaced unstable comminuted fractures of the distal radius. The JESS fixator consistently restored the palmar tilt of the distal radius, and loss of ulnar tilt and radial height was acceptable.…”
Section: Figure 1: Modified Gartland and Werley Scoring Systemmentioning
confidence: 92%
“…Non-spanning external fixators have the theoretical advantage of allowing wrist mobilization early with the attendant advantages, 4 but often the fixation of pins in small comminuted distal fragments is unsatisfactory. The dynamic external fixators have been developed to provide spanning fixation and at the same time allowing mobilization of the wrist while reduction and fixation are maintained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This increases the pain of sufferers and the curing time is lengthened correspondingly. In some cases, external fixations are used for some weak people, aged people and some people who are seriously suffering from medical disease (Keeling et al, 2008;Hove et al, 2010;Willie et al, 2009). Comparing this to the former method, this method can effectively decrease the time for treatment, but it still has some shortcomings.…”
Section: Introductionmentioning
confidence: 99%